Reforming Standard Essential Patents: Trade, specialisation, and international jurisprudence - Fredrik Erixon; Oscar Guinea (European Centre for International Political Economy (ECIPE), 2023)
The European Commission is considering a radical overhaul of the system governing Standard Essential Patents (SEPs). A leaked proposal suggests that the Commission wants to take control over the registration of SEPs, take efforts to regulate their essentiality, and intervene in negotiations over royalty rates if parties do not come to an agreement. The underlying assumption is that such a system will benefit SEP implementers and the European economy, and that the common holders of SEPs will be cut down a size or two. Using data on trade, specialisation, and market revenues, this paper comes to a different conclusion: the EU economy is likely to be a net loser if the balance between holders and implementers is changed. Moreover, there is a general and fundamental interest for Europe to preserve a system of standards and SEPs that allows it to punch above its weight in international policies and practices in standards and patents.
Keywords: 330